HAMBATAN SISTEM PERADILAN ELEKTRONIK DI PENGADILAN AGAMA AMBON KLAS IA - Mohdar Yanlua; Tuti Haryanti; Abdul Kasim Abdul Kasim Peisama (TAHKIM, 2022)
The birth of the e-court application has changed the justice system in Indonesia. The Supreme Court continues to encourage every judicial institution to implement Perma's orders, including the Ambon Religious Court. This study aims to examine the implementation and obstacles of the electronic justice system in the Ambon Class IA Religious Courts.The research method used is empirical with primary and secondary data sources. Primary data were obtained by conducting in-depth interviews with several informants at the Ambon Religious Court. Secondary data, namely reviewing and analyzing legal provisions, articles related to the object of study. The results showed that the Ambon Religious Court had attempted to implement the electronic justice system, but it was not yet optimal. There are several obstacles encountered in its implementation, namely the low ability of justice seekers to use the e-court feature, justice seekers do not know the utility value of e-court and inadequate internet facilities. Therefore, the Ambon Religious Courts need to conduct education and socialization of e-courts to realize the ideals of the Supreme Court in modernizing the judiciary without deviating from the principles of civil procedural law.Keywords: Electronic Justice System, Barriers, Ambon Religious Court